Export-Oriented Enterprises of the Cotton Textile Industry - Luptullaevich, Khalikov Tolibjon (International Journal of Human Computing Studies, 2023)
Cotton harvesting factories were established as separate independent enterprises. Their products are used as raw materials in other textile factories or in other industries. The capacity of cotton-spinning factories is determined by the number of cameras and the number of products produced. The most effective organization of serial production at textile enterprises. It is desirable to constantly plan production in market conditions.